Homocysteine is not an indicator of restenosis risk after percutaneous transluminal coronary angioplasty - (:unkn) unknown (My University, 2000)
Objective: Elevated homocysteine levels have been associated with increased risk of atherosclerotic vascular disease. The possible. association of homocysteine with restenosis after percutaneous transluminal coronary angioplasty (PTCA) has not been widely investigated. Methods: In order to determine if a relationship exists between serum homocysteine levels and restenosis after PTCA, serum homocysteine level were determined in 204 patients who underwent a successful PTCA procedure and stant implantation. The patients were followed with clinical examinations and exercise tests at 1, 3, and 6 months, and a control coronary angiography was performed after 6 months to evaluate restenosis. Homocysteine levels were determined with fluorescence polarization immunoassay. Results: Of the 146 patients who underwent angiographic evaluation, 57 (39 %) had restenosis, whereas 89 (61%) did not. The homocysteine distributions were compared in these two groups of patients. Although the average homocysteine levels were higher in the restenosed group, the difference was not statistically significant. Conclusion: Because of its wide distribution, serum homocysteine values do not seem to be a useful indicator for the risk of restenosis after PTCA.
Keywords: Homocysteine; PTCA; Restenosis